RISK ANALYSIS OF ROCK FALLS AT THE IBITIPOCA STATE CONSERVATION PARK AND ITS SURROUNDINGS, MINAS GERAIS STATE, BRAZIL - Geraldo César Rocha; Sarah Lawall; Fillipe Tamiozzo Pereira Torres- (Sociedade & Natureza)
The Ibitipoca region is located at the southeast part of Minas Gerais state, in Brazil (figure1).It is composed by the Ibitipoca State Conservation Park, a conservation unit that occupies thehighest areas of the Ibitipoca Range, and by the surroundings of those mountains, with lowesttopography, where there are farms and rural communities. This enveloping area of the parkfunctions as a buffer zone, protecting the direct impact of tourism at the park, with the aid offorests and biological corridors.This region occupies an area of 14000 ha, and the conservation unit itself covers 1480 ha,protecting important remainings of the Atlantic Tropical Forest, as well as endemic plants,and several caves developed in quartzites, CORREA NETO (1997); ZAIDAN (2002).The research group on Environmental Zoning and Risk of the Federal University of Juiz deFora has worked in the region since 1995, developing the environmental mapping of theregion, with the target to furnish data as a basis for the Management Plan of the whole area.The research has shown the extreme environmental fragility of the area, in respect not only tothe biotic system, as well as to the physical components, ROCHA et all (2002); ROCHA et all(2001); ROCHA e MACIEL (2000); ROCHA et all (2000).The vertiginous increment of the eco-tourism in the region, without rigid normalization ofthis activity, has magnified the environmental impacts, and also the risks to the tourist.The environmental data base already done permits the assessment of several important topicsto the management of the area; one of these is the risk of rock falls, a menace to the touristsand inhabitants of the region. In this way, the objective of this work is the development of theRock Fall Risk Map of the area, as a contribution to the sustainable management of theIbitipoca region.